Mini-Hydro Project for Street Lighting - Ruzaini Nazli, Nur Aelya; Samsudin, Nur Syazwina; Kamaruddin, Muhammad Kamal Hakim; Nor Baizura Hamid (Multidisciplinary Applied Research and Innovation, 2024)
Hydro energy is widely used around the world and can generate electricity using the flow of moving water. Hydroelectric energy can be saved and used to address the problem of the electrical supply if it is stopped. The problem of insufficient electricity supply in rural areas will cause many problems for road users. Furthermore, if the electricity supply is cut off, hydroelectric energy can be stored, allowing the electricity supply problem to be solved. One of the causes of road accidents is a lack of street lighting on the roads, particularly in rural areas. This study discusses the benefits and application of hydroelectric energy in supplying electricity, particularly to street lights in rural areas. The objective of this study is to get user feedback on the importance of street lights while driving. Besides, to design a mini-hydro project that uses water turbines for street lighting as a new source of power, The output voltage, current, and power of the mini-hydro project have also been determined. The method used to achieve the objectives was a survey on Google Forms. Next, the model was tested by using a multimeter to measure the voltage of the power current. The first objective demonstrates that 98.4% of the 128 respondents to the survey concurred that street lights are essential for safe driving. In view of this, 96.1% of respondents concurred that one of the elements influencing driving safety is the intensity of street lights. Next, the model was successfully developed based on user suitability as a result of the research done. This model can generate voltage and power of 5.181 V and 0.988 kΩ, respectively. In conclusion, this study achieved all the objectives of the mini-hydro project’s development.